Letter (copy) : Milk for Spain - Tewson, Vincent
032-0170-001 International. HVT/EAB/AT/350 21st December, 1938. Mr. Winstanley, Co-operative Wholesale Society Ltd., 1 Balloon Street, Manchester 4. Dear Mr. Winstanley, MILK FOR SPAIN. We desire to confirm our telephone conversation with your Department yesterday, when we ordered 60,000 kilos of Dutch Full Cream Roller Process Milkpowder, 24% Butterfat, at £2.10.6d. per 50 kilos, packed in paper lined cases, c.i.f. Cerbere. The consignment should be addressed as previously to Senor Santiago, Fondo Internacional de Solidaridad, Aragon 500, Barcelona. We shall be glad if you can make arrangements for an early delivery. With the Season's greetings, Yours sincerely, Assistant Secretary. 292/946/32/170